Memahami Filsafat Manusia Melalui Video Animasi - Putri, Fildzah Rudyah (Jendela Akademika, 2023)
This paper is about the implementation of community service activities carried out by lecturers of the Faculty of Psychology Universitas Negeri Jakarta for the general public. Community service activities are carried out by making animated videos about Human Philosophy. Rumors circulating in society that studying philosophy is difficult and can lead people to get lost in religion need to be changed. Though Human Philosophy essentially invites people to think critically and logically. A thing that is needed in today's era. Therefore, an animated video with an attractive appearance and light language is made to increase people's understanding of Human Philosophy, so that these stigmas can change. Animated videos are created and uploaded on the YouTube page to make it easier for the general public to access them. As a result, of all the people who filled out the feedback questionnaire, there were 52% of the people who thought that the video was very clear and able to increase their understanding.